2018
DOI: 10.1103/physrevb.97.205439
|View full text |Cite
|
Sign up to set email alerts
|

Measuring anisotropic spin relaxation in graphene

Abstract: We compare different methods to measure the anisotropy of the spin lifetime in graphene. In addition to out-of-plane rotation of the ferromagnetic electrodes and oblique spin precession, we present a Hanle experiment where the electron spins precess around either a magnetic field perpendicular to the graphene plane or around an in-plane field. In the latter case, electrons are subject to both in-plane and out-of-plane spin relaxation. To fit the data, we use a numerical simulation that can calculate precession… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
4
22
2
Order By: Relevance
“…It has to be noted that fabricating spin selective contacts in graphene that was hydrogenated by this method proved to be difficult in general. Further, the extracted spin lifetime of τ s = 146 ps is much smaller than what was observed in pristine graphene with tunneling contacts produced by the same method 19 .This is in contrast to the findings of Wojtaszek et al who observed an increase in spin lifetime after treating pristine graphene with hydrogen plasma 20 . This small value for the spin lifetime can be caused by either an increased contact-induced spin relaxation due to an increase in the number of pinholes 21 or due to increased spin relaxation by the presence of hydrogen atoms acting as magnetic impurities 22 .…”
Section: Inverse Spin Hall Effect In Hydrogenated Graphenecontrasting
confidence: 59%
“…It has to be noted that fabricating spin selective contacts in graphene that was hydrogenated by this method proved to be difficult in general. Further, the extracted spin lifetime of τ s = 146 ps is much smaller than what was observed in pristine graphene with tunneling contacts produced by the same method 19 .This is in contrast to the findings of Wojtaszek et al who observed an increase in spin lifetime after treating pristine graphene with hydrogen plasma 20 . This small value for the spin lifetime can be caused by either an increased contact-induced spin relaxation due to an increase in the number of pinholes 21 or due to increased spin relaxation by the presence of hydrogen atoms acting as magnetic impurities 22 .…”
Section: Inverse Spin Hall Effect In Hydrogenated Graphenecontrasting
confidence: 59%
“…Here we study τ ⊥ and τ in fully hBN encapsulated BLG using oblique spin precession. Our results show that, in contrast with monolayer graphene [17,[19][20][21], at temperatures below 300 K, the ratio τ ⊥ /τ is significantly above 1 over the full measured range of n. At 75 K we observe a dependence of τ ⊥ /τ on the carrier concentration which increases from 3.5 ± 1 at n = 6 × 10 11 cm −2 to 8 ± 2 at the CNP confirming the role of the spinvalley coupling on the spin transport. The anisotropy at the CNP is comparable to graphene/TMD systems [6,7].…”
mentioning
confidence: 83%
“…Meanwhile, spin relaxation owing to strain-induced gauge fields 60 is predicted to yield ζ > 1. Recent measurements of graphene on SiO 2 substrates 54,109,110,113,129 have revealed ζ ≈ 1. This rules out the DP mechanism, as well as strain and corrugation, as the main drivers of spin relaxation in these measurements and further supports magnetic impurities or spin-pseudospin coupling.…”
Section: History Of Spin Transport In Graphene 21 Graphene On Traditmentioning
confidence: 99%